The aesthetics of contemporary Arabic calligraphy in Duaa Alashari painting: The story of love / Duaa Mohammed Alashari - Mohammed Alashari, Duaa (Universiti Teknologi MARA, Perak, 2022)
Arabic calligraphy is known as Islamic calligraphy. Alashari artworks introduce Arabic calligraphy as an art form to contemporary viewers and show them how to identify, understand and appreciate its varied styles and modes. This paper aims to present the aesthetics of contemporary Arabic calligraphy and the spirituality in the Alashari painting. The method used in this study is the descriptive-analytical method. The study concluded that this painting expresses movement, rhythm and dynamism as seen through the calligraphic marks and dripping.